1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<161::aid-ijc2>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of childhood leukemia in Southern Ontario, Canada, and exposure to magnetic fields in residences

Abstract: A population-based case-control study was conducted in Ontario, Canada, to assess the relation between the risk of childhood leukemia and residential exposure to magnetic fields. Participating subjects consisted of 201 cases, diagnosed at 0 to 14 years of age during 1985-1993, ascertained from the records at the Hospital for Sick Children (Toronto), and 406 individually matched controls. Where possible, point-in-time measurements of magnetic fields were made in all residences occupied by subjects during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Two other recent studies were excluded. Green et al (1999) presented only analyses based on quartile categories, resulting in upper cut points of only 1.3–1.5 mG. This study was excluded because the use of such low cut points strongly influenced estimates from earlier studies (Greenland, Sheppard, Kaune, Poole and Kelsh, 2000); it did, however, report positive associations on contrasting the top and bottom quartiles.…”
Section: Magnetic Fields and Childhood Leukaemiamentioning
confidence: 99%
“…Two other recent studies were excluded. Green et al (1999) presented only analyses based on quartile categories, resulting in upper cut points of only 1.3–1.5 mG. This study was excluded because the use of such low cut points strongly influenced estimates from earlier studies (Greenland, Sheppard, Kaune, Poole and Kelsh, 2000); it did, however, report positive associations on contrasting the top and bottom quartiles.…”
Section: Magnetic Fields and Childhood Leukaemiamentioning
confidence: 99%
“…Initial studies characterized field levels using short-term, or "spot," measurements taken immediately outside (23) or within residences (12), the latter obtained in the child's and parents' bedrooms. Subsequently, 24-hr measurements were obtained in rooms in which subjects spent a substantial proportion of time, based on interview data (9,15,19,21,(33)(34)(35)(36)(37). Such measurements are made after diagnosis, but unlike measurements based only on power lines, these inhome measurements reflect all sources of magnetic fields in the residence (38).…”
Section: Residentialmentioning
confidence: 99%
“…In residential studies assessing exposure using spot and/or 24-hr or longer area magnetic field measurements, increases in leukemia, ranging from 1.3-to 1.5-fold elevated, were reported for children with average magnetic field exposures ≥0. (34,79), and an odds ratio of 1.1 (95% CI = 0.31-4.06) was linked with point-in-time measurements ≥0.13 µT taken in the child's bedroom in a study in southern Ontario, Canada (based on 21 cases) ( Table 1) (36). The latest study is from Germany and showed a relative risk of 1.6 (0.7-3.7) for 0.2 µT and 3.2 (1.3-7.8) for nighttime exposure (80).…”
Section: Childhood Cancermentioning
confidence: 99%
“…According to [3], increased risk starts at level several hundred times lower than the reference level. Studies reported in [4] indicate that increased risk starts as low as 0.4 µT or even lower. According to [5], [6], the average level of magnetic flux density ranges from 0.025 μT to 0.07 μT at homes and typically is ten times higher at workplaces.…”
Section: Introductionmentioning
confidence: 98%